Integrated Transcriptomic and Targeted Metabolomic Analysis Reveals the Key Genes Involved in Triterpenoid Biosynthesis of Ganoderma lucidum - Xiaolan Xu; Chunxia Li; Fangjing Wu; Shuangshuang Zhao; Tiqiang Chen; Haihong You; Yijie Lin; Xiaoxing Zou (Journal of Fungi)
Ganoderma lucidum is a traditional Chinese medicinal fungus, and ganoderma triterpenoids (GTs) are one of the main bioactive compounds. These compounds have various pharmacological functions, including anti-tumor, antioxidant, anti-inflammatory, liver-protective, and immune-regulating effects. However, the manner in which they accumulate, and their biosynthesis mechanisms remain unclear. To screen for the genes that are involved in the biosynthetic pathway of GTs, this study analyzed the differential metabolites and differentially expressed genes (DEGs) among different growth stages of G. lucidum, including the primordia (P), the matured fruiting body (FM), and the post-spore fruiting bodies (FP) using targeted metabolomics and transcriptomics analysis, respectively. The results showed that a total of 699 components were detected, including lignans, terpenoids, amino acids and derivatives, and phenolic acids, among others. Among them, a total of 112 types of triterpenes were detected. Compared with the primordia, there were eight differential metabolites of triterpenoids, with three decreasing and five increasing in the FM stage. A comparison between the FM stage and the FP stage revealed that there were 13 differential metabolites of triterpenoids. A transcriptomics analysis showed that there were 371 DEGs in the P_vs_FM group, including 171 down-regulated genes and 200 up-regulated genes. In the FM_vs_FP group, 2567 DEGs were identified, with 1278 down-regulated genes and 1289 up-regulated genes. Through targeted metabolomics and transcriptome correlation analysis, six TFs and two CYP450s were significantly associated with four triterpenoid components. The results showed that these TFs and CYP450s were positively or negatively correlated with the four triterpenoid components. In addition, interestingly, some flavonoids and phenolic compounds, which have been reported in plants, were also detected in G. lucidum, indicating that it has the potential to be engineered into a strain capable of synthesizing flavonoid compounds. This study provides useful information about key genes involved in GT biosynthesis, but further exploration and in-depth research are needed to better understand the functions of these genes.